Motion correction in PET/CT - Schäfers, K. P.; Dawood, M.; Lang, N.; Büther, F.; Schäfers, M.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2005)
Motion in PET/CT leads to artifacts in the reconstructed PET images due to the different acquisition times of positron emission tomography and computed tomography. The effect of motion on cardiac PET/CT images is evaluated in this study and a novel approach for motion correction based on optical flow methods is outlined. The Lukas-Kanade optical flow algorithm is used to calculate the motion vector field on both simulated phantom data as well as measured human PET data. The motion of the myocardium is corrected by non-linear registration techniques and results are compared to uncorrected images.
Keywords: PET/CT